Health and safety at work in SMEs: strategies for employee information and consultation (Dublin, 2010)
"Small and medium-sized enterprises face a number of difficulties in complying with occupational health and safety (OSH) regulations owing to fewer resources and less awareness of the costs of non-compliance in terms of higher risks. Employee OSH representatives are frequently lacking, especially in smaller companies, making it more difficult to implement the participatory approach envisaged by the 1989 EU Framework Directive on health and safety. Consultation on changes to organisation and working conditions, workplace learning opportunities and job security all contribute positively to improving employee information on OSH risks at work. One approach that appears promising when dealing with this gap is free counselling combined with discounts on insurance premium for those achieving substantive reductions in their accident rates, and territorial employee representatives. "